Collinear setup for delay control in two-color attosecond measurements. (20th April 2020) - Ahmadi, H; Kellerer, S; Ertel, D; Moioli, M; Reduzzi, M; Maroju, P K; Jäger, A; Shah, R N; Lutz, J; Frassetto, F; Poletto, L; Bragheri, F; et al.
Abstract: We present a compact experimental setup for performing attosecond-pump-infrared-probe experiments with long-time delay stability. The robustness of the setup is demonstrated over a two-day acquisition time in two-photon photoionization of argon in the photon-energy range 17−33 eV. The propagation of the input infrared pulse, as driving pulse for the high-order harmonic generation process and for the generation of the sidebands of the main photoelectron peaks, through the main optical components is simulated and discussed. Our setup allows us to perform attosecond experiments with an overall stability of ± 40 as.